Distribution of some heavy metals in Kelang River Estuary - Singh, Amargit (1984)
The distribution of copper, lead, mercury and zinc in the Kelang River estuary were studied. Six stations were selected for sampling. Two of these stations were in the fresh waterregme while the rest were in the estuarine zone. The dissolved and total copper, lead and zinc concentrations in the water column were determined by meatomic absorption spectrophotometer after chelat on and extraction with solvent. The total man ganeseandir on concentration in wateraswell as the extract ablecopper,lead and zinclevelsin the sediment were studied. The total mercury content in the water column, sedimentand fishes was determined by cold -vapour atomicab sorptions pectropho to metric method. The heavy met alcontents in six species of fishes, namely P1otos usanguil1aris, Ariusthal assinus, Dasyatiszugei, Gastrophysu slunaris, Setipinna and Johnius carutta were studied. some physico-chemical parameters of the water column such as salinity, dissolved oxygen content, watervelocityand pH were determine at different depths and stations.